2013
DOI: 10.1111/febs.12355
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycosides correct aberrant splicing of IKBKAP‐encoded mRNA in familial dysautonomia derived cells by suppressing expression of SRSF3

Abstract: The ability to modulate the production of the wild-type transcript in cells bearing the splice-altering familial dysautonomia (FD) causing mutation in the IKBKAP gene prompted a study of the impact of a panel of pharmaceuticals on the splicing of this transcript, which revealed the ability of the cardiac glycoside digoxin to increase the production of the wild-type, exon-20-containing, IKBKAP-encoded transcript and the full-length IjB-kinasecomplex-associated protein in FD-derived cells. Characterization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…In the same study, an additional exonic splicing silencer (ESS1) was also identified. However, deletion and mutagenesis studies indicate that ESS1 has lower silencing capability than ESS2, possibly due to the existence of an overlapping SE element (17,32). We hypothesized that ESS1 and ESS2 may function by binding hnRNP A1, and that the intronic hnRNP A1 binding site could represent an ISS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, an additional exonic splicing silencer (ESS1) was also identified. However, deletion and mutagenesis studies indicate that ESS1 has lower silencing capability than ESS2, possibly due to the existence of an overlapping SE element (17,32). We hypothesized that ESS1 and ESS2 may function by binding hnRNP A1, and that the intronic hnRNP A1 binding site could represent an ISS.…”
Section: Resultsmentioning
confidence: 99%
“…Both silencers were shown to inhibit exon 20 inclusion, though ESS2 appeared to be a stronger inhibitor than ESS1, which is consistent with the fact that our SPRi analysis demonstrated more hnRNP A1 binding to the ESS2 than to ESS1. Furthermore, in another study investigating splicing of deletion mutants of an FD- IKBKAP minigene, only a deletion that disrupted ESS2, but not a deletion that disrupted the ESS1 silencer, restored splicing of exon 20 (17). We show that specifically mutating the hnRNP A1 binding sequence in either of the two exonic silencers, ESS1 and ESS2, completely restores splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Although further transcriptome and mechanistic studies will be required, the effects were remarkably selective and at least one of the compounds appeared to specifically stabilize base pairing between U1 snRNA and particular sequence features of the SMN2 exon 7/intron junction. In this regard, it is interesting that a number of compounds, including kinetin , cardiac glycosides , and RECTAS , have been shown to facilitate recognition of the 5′ SS of the IKBKAP gene mutated in FD, perhaps by stabilizing particular sets of base‐pairing interactions, as proposed for SMN2. Another interesting therapeutic lead would be the use of compounds able to modulate particular secondary pre‐mRNA structures, as shown for MAPT exon 10 .…”
Section: Considering Therapeutic Approachesmentioning
confidence: 99%
“…Digoxin also regulates the splicing of HIV transcripts [74]. Its closely related form digitoxin down-regulates SRSF3 (SRp20) [75,76], as well as TRA2β [76]. Interestingly, the suppressive effect of digoxin on SRSF3 increases the exon 20-containing wild type transcripts of the IkappaB kinase complexassociated protein (IKAP) gene in cells from familial dysautonomia (FD) patients [74].…”
Section: Small Molecules Targeting Aberrant Splicingmentioning
confidence: 99%